Avaliação do perfil clínico, laboratorial e molecular de cães suspeitos de Erlichiose e tratados com Doxiciclina - Silva, Nicilene Cardoso (2012)
This study aimed to describe the clinical and molecular profile, and evaluating the evolution of an standard treatment with doxycycline 10 mg/kg every 12 hours (BID), for three weeks to natural Ehrlichia canis infection.18 mongrel dogs were selected, both sexes, mean age 3,4 ± 1,5 years old, showing clinical symptoms of the disease and a history of tick infestation.The animals were treated with doxycycline 10mg/kg orally (PO), BID, for 21 consecutive days and assessed the week before starting treatment (d-7) and on the first day (d0), day 14 (+14 d) and day 21 (d +21) treatment. At each assessment was made on history, haematological and biochemical analysis and PCR. Although there was a significant improvement in the general state of the dogs, it was noted that the hematological had not yet established fullness in all animals after the treatment with doxycycline. The PCR was positive for E. canis in 3 animals at pre-treatment. An animal was positive during and at the end of treatment. After treatment, none of the animals showed clinical manifestations observed previously, only one animal remained positive for molecular testing, suggesting resistance to treatment in the dose used. The study concluded that the clinical, haematological and biochemical changes observed in dogs infected by E. kennels are nonspecific; 21 days of treatment for improvement in anemia and thrombocytopenia, and WBC did not follow a pattern among animals. The study concluded that the findings clinical and laboratory are general and non-specific. The diagnosis should be based on clinical, hematological, serum titers of anti-E. canis and confirmed by the presence of genetic material of the body in the circulating blood.